2018
DOI: 10.1002/anie.201806261
|View full text |Cite|
|
Sign up to set email alerts
|

Mechanistic Studies on the Organocatalytic α‐Chlorination of Aldehydes: The Role and Nature of Off‐Cycle Intermediates

Abstract: Herein we report the isolation and characterization of aminal intermediates in the organocatalytic α-chlorination of aldehydes. These species are stable covalent ternary adducts of the substrate, the catalyst and the chlorinating reagent. NMR-assisted kinetic studies and isotopic labeling experiments with the isolated intermediate did not support its involvement in downstream stereoselective processes as proposed by Blackmond. By tuning the reactivity of the chlorinating reagent, we were able to suppress the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…19 In 2009, Mac-Millan demonstrated that 3c can be used for the SOMO chlorination of aldehydes. 18 We started our own investigations in 2011 by initially using the MacMillan's SOMO protocol 20 but later moved to the combination of 3c (20 mol%) and NCS in acetonitrile 21 due to side reactions 22 of radical intermediates in the SOMO chlorination of terpene aldehydes.…”
Section: Scheme 2 α-Chlorination Of Aldehydes (2004-2009)mentioning
confidence: 99%
See 2 more Smart Citations
“…19 In 2009, Mac-Millan demonstrated that 3c can be used for the SOMO chlorination of aldehydes. 18 We started our own investigations in 2011 by initially using the MacMillan's SOMO protocol 20 but later moved to the combination of 3c (20 mol%) and NCS in acetonitrile 21 due to side reactions 22 of radical intermediates in the SOMO chlorination of terpene aldehydes.…”
Section: Scheme 2 α-Chlorination Of Aldehydes (2004-2009)mentioning
confidence: 99%
“…Motivated by the isolation and X-ray crystal structure analysis of several aminals derived from the 3 rd generation MacMillan catalyst 3c, 22 we aimed at extending the structure determination to the 1 st and 2 nd generation MacMillan catalysts 3a and 3b. The 1 H-NMR spectra of the isolated and crystallographically characterized aminals were compared to the NMR spectra recorded during the reactions and our stereochemical assignments were compared to those reported in the literature.…”
Section: Aminals Derived From 1 St 2 Nd and Rd Generation Macmillanmentioning
confidence: 99%
See 1 more Smart Citation
“…Employing electron-rich chlorine source 10 [20] at 10 °C gave 2αchloro-sclareolide (9) in a yield of 41% within 100 min using a 3Dprinted photoreactor (for details, see the Supporting Information). To prove scalability, this transformation was repeated on gram scale and gave a similar yield of 38%.…”
mentioning
confidence: 99%
“…[19] We envisaged that a favorable photon transfer in flow could accelerate site-selective chlorination of (+)-sclareolide (8) through decatungstate catalysis. Employing electron-rich chlorine source 10 [20] at 10 °C gave 2αchloro-sclareolide (9) in a yield of 41% within 100 min using a 3Dprinted photoreactor (for details, see the Supporting Information). To prove scalability, this transformation was repeated on gram scale and gave a similar yield of 38%.…”
mentioning
confidence: 99%